Analyse empirique de la relation entre le changement climatique et la sécurité alimentaire à la Dominique - Louis Dupont (Études Caribéennes)
The goal of this study is to evaluate the extent to which climate change affect the food security in Dominica, by using climatic and economic variables such as temperature, precipitations, CO2 emissions, economic growth and inflation rates. To address this evaluation, an ARDL model is used for the period 1995-2019. According to this study, the temperature has a negative impact, short term on food security. It is also true that CO2 emissions have the same negative impact long term/short term on food security, while the economic growth effects positively long-run food security. The precipitations coefficient is significatively positive short-run and long-run. On the other hand, the inflation coefficient paradoxaly does not have the right sign and have a weak impact on food security. In addition, hurricane events, as expected, bring negative impact on food security short run.